The Influence of Person Job Fit and Person Organization Fit on Organizational Commitment - Harefa, Cindy Eunike; Dirbawanto, Nana Dyki (Formosa Journal of Applied Sciences, 2024)
This research aims to analyze the influence of person job fit and person organization fit on organizational commitment (study of employees of PT. Bina Media Perintis Medan). The influence between person job fit and person organization fit will be analyzed partially and simultaneously on organizational commitment. The form of research used for this research is quantitative with an associative approach. Sampling was carried out using a purposive sampling technique and used 40 respondents as samples. The results of the research conducted show that the variables person job fit (X1) and person organization fit (X2) have a significant effect on organizational commitment. The person job fit and person organization fit variables simultaneously influence organizational commitment (Y) with an R value of 0.929. Through the adjusted R square value, it is known that the person job fit and person organization fit variables contribute 85.5%.